Synthesis, Absorption, Distribution, Metabolism, Excretion, Toxicology (ADMET) and molecular docking studies of some pyridin-2(1H)-one derived from a Apocynin in Thi-Qar Governorate - Thejeel, Entedhar; Athraa Hameed Mekky (University of Thi-Qar Journal of Science, 2023)
The present study includes synthesized of some pyridin-2(1H)- one of 1-(4-hydroxy-3-methoxyphenyl) ethan-1-one. The [ 6-(4-hydroxy-3-methoxyphenyl) - 4 - (4-methoxyphenyl) - 2 - oxo-1,2-dihydropyridine - 3- carbonitrile, 4 - (4-bromophenyl) - 6 -(4-hydroxy-3-methoxyphenyl)-2-oxo-1,2- dihydropyridine - 3- carbonitrile, 4 - (4-bromophenyl) – 6 - (4-hydroxy-3-methoxyphenyl)-2-oxo-1, 2 - dihydropyridine - 3-carbonitrile] derivatives have been synthesized by cyclization reaction of the 1-(4-hydroxy-3-methoxyphenyl)ethan-1-one with various aldehydes (4-methoxy benzaldehyde, 4-bromo benzaldehyde ,4-dimethyamino benzaldehyde) respectively and ethyl cyanoacetate in the presence of ammonium acetate. The structures of the prepared compounds were confirmed by the different available spectroscopic methods, such as FTIR, 1H-NMR, 13C-NMR and mass spectroscopy. The physical properties were assessed. The antioxidant activity of the synthesized compounds was evaluated by the use of 2,2- diphenyl-1-picrylhydrazyl. The compounds 4-(4-bromophenyl)-6-(4-hydroxy-3-methoxyphenyl)-2-oxo-1,2-dihydropyridine-3-carbonitrile,and4-(4-bromophenyl)-6-(4-hydroxy-3-methoxyphenyl)-2-oxo-1,2-dihydropyridine-3-carbonitrile, showed the highest activity as antioxidants (79.05, 67.28)%, which can be compared with ascorbic acid 82.71%, while the antioxidant activity of compound 6-(4-hydroxy-3-methoxyphenyl)-4-(4-methoxyphenyl)-2-oxo-1,2-dihydropyridine-3-carbonitrile, showed less effectiveness for the antioxidant 17.55% at a concentration of 12 ppm. Also, the prepared compounds were assessed for in vitro biological activity against the two types of bacteria [staphylococcus aureus, Escherichia coli] respectively which displayed moderate inhibition. In an attempt to understand the ligand–protein interactions in terms of the binding affinity, docking studies were performed using Py-Rx and BIOVIA\Discovery Studio 2021 for the compounds.  the binding affinities calculated were in agreement with the minimum inhibitory concentration [MIC] values.